Perbandingan Efektivitas Pelaksanaan Supervisi Akademik dan Supervisi Klinis oleh Kepala Sekolah dalam Meningkatkan Profesionalisme Guru pada SMP 3 Bae Kudus - Lina Handayani; Sukirman Sukirman (Universitas Muhammadiyah Enrekang, 2020)
Education is a process of building human quality. Education is carried out with various educational plans, implementation of national education standards and supervision to produce evaluations. However, the implementation of academic supervision still has weaknesses, so a comparison with clinical supervision that is more focused on improvement efforts is needed. The research objective is to analyze the factual conditions of academic supervision and to compare the effectiveness of academic supervision with clinical supervision. This research was conducted with a descriptive qualitative approach. The results of the study, the implementation of academic supervision by forming a supervision team was not in accordance with the essence of academic supervision that was carried out to develop the ability of teachers, because there were teachers who had problems in teaching and learning process that were not getting optimal treatment. The way to increase professionalism is by clinical supervision by the principal so that it can be used to find solutions to educational problems, especially the teaching and learning process. Conclusion clinical supervision is more appropriate to be applied in schools that still have problems in the teaching and learning process.